Pengaruh Inovasi Produk dan Kreativitas Produk terhadap Keunggulan Bersaing : Survei pada Konsumen Samudra Bordir Tasikmalaya - Rismawan; Budhi Wahyu Fitriadi; Barin Barlian (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the simultaneous and partial effect of product innovation and product creativity on competitive advantage in Samudra Bordir Tasikmalaya. The research method used in this study is a quantitative approach with a survey method. The population in this study amounted to 100 respondents. The type of data used in this study is primary data obtained through a questionnaire. The data analysis used is the classical assumption test and multiple regression analysis using SPSS version 24. The results of this study indicate that product innovation and product creativity simultaneously have a significant effect on competitive advantage in Samudra Bordir Tasikmalaya. Product innovation partially has a significant effect on competitive advantage in Samudra Bordir Tasikmalaya. Product creativity partially has a significant effect on competitive advantage in Samudra Bordir Tasikmalaya.